Chemistry : science of change - Oxtoby, David (Thomson-Brooks/Cole, 2003)
The treatment of quantitative subject matter is complete and rigorously correct." "Your book has always had great examples and end of chapter problems." "The accuracy of the information is, as far as I can tell, flawless. I know of no other general chemistry book as accurate as the Oxtoby texts." "The strategy statement (in the worked example) will help the student both to understand the solution and to view it as more than just an algorithm for solving "this type" of problem."